Aspects of radiation damage effects in Fe-Cr alloys from the point of view of atomistic modeling - Terentyev, D.; Olsson, P. (Вопросы атомной науки и техники, 2009)
Fe-Cr alloys are the basis of high-Cr ferritic steels, which are the candidates for the structural materials for near future power plants. Recently, a significant effort has been put in the development of theoretical models dealing with the response of Fe-Cr alloys to irradiation. Here, we give a brief overview of the current level of understanding of radiation damage in Fe-Cr alloys, based on the most recent results. In particular, we review and summarize data obtained using different atomistic modelling techniques in order to refine the most important findings achieved over the past few years.